DIGITAL ADAPTATION IN THE E-POSTAL SERVICE SYSTEM AT THE BATAM CITY IMMIGRATION OFFICE - Mulda, Rahmayandi; Solihin, Muhammad; Setyobudi, Yustinus Farid; Sari, Meri Enita Puspita; Pratiwi, Diah Ayu; Miguel, Ibrahim Sahidjun (Jurnal EL-RIYASAH, 2025)
Digital transformation in public services is a strategic step in improving service quality and efficiency, including in the immigration sector. This study examines digital adaptation through the implementation of the E-Passport system at the Batam City Immigration Office using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. The UTAUT model evaluates four main constructs: performance expectancy, effort expectancy, social influence, and facilitating conditions that influence user acceptance of technology. The results showed that the M-Passport application and the digital infrastructure provided significantly increased users' perceived ease and trust in the service. In addition, social support and supporting facilities at the immigration office also strengthen the adoption of this system by the community. However, there are challenges for those with limited digital access. Therefore, an inclusive and educative service strategy is still needed to ensure the overall success of technology adaptation. This study recommends continuous evaluation and improvement of digital features to optimize public service transformation.